Relaxamento muscular progressivo de Jacobson: fundamentação teórica, aplicação e questões atuais de pesquisa - Tófoli Neto, Fernando (Universidade Federal de São Carlos, 2021)
Anxiety and stress reactions are present in the everyday life of our species. Different assessment and intervention procedures take into account the patient's life history, organic condition, and environmental aspects that trigger emotional responses. The progressive muscle relaxation technique, developed by Edmund Jacobson in the early 20th century, pioneered understanding of the functions of muscle contraction and relaxation in producing states of tranquility and self-control in typically anxious patients. The present paper aims to provide a characterization and description of progressive relaxation. To do so, we started by consulting and analyzing primary and secondary sources in order to systematize the fundamentals of this therapeutic technique, its historical context, evidence of effectiveness, and modifications/adaptations it has undergone until today. The primary sources consist of Edmund Jacobson's textual productions, and the secondary ones of research reports using the technique or about the technique. In the end, we conclude that it is important in the academic environment and as an intervention offered to patients who need to learn emotional self-control.
Jacobson's progressive muscle relaxation: theoretical foundation, application and current research issues
Keywords: Relaxamento muscular progressivo; Reações emocionais; Ansiedade e estresse; Progressive muscle relaxation; Emotional reactions; Anxiety and stress; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA